A Multi Objective Solution to Integrated Power System in the Presence of Thyristor Controlled Series Compensator - Yaseen, MD.; Bali, Sravana Kumar (Contemporary Mathematics, 2024)
The current geopolitical climate has highlighted the significance of maximizing the world’s energy potential. The optimal use of available assets lowers the cost of electricity to customers. This study proposes a multi-objective ideal power flow for a composite transmission network with FACTS devices. The multi-objective function used in this work is a novel approach. Objectives include minimizing voltage variance, power loss, and negative social welfare (NSW). A Thyristor Controlled Series Compensator (TCSC) FACTS device is employed in this work to test on IEEE 57 bus system. Moth Flame Optimization Algorithm maximized the objective function. The results are detailed, compared, and assessed.